A fast and sensitive new satellite SO2 retrieval algorithm based on principal component analysis: Application to the ozone monitoring instrument. Issue 23 (11th December 2013) - Li, Can; Joiner, Joanna; Krotkov, Nickolay A.; Bhartia, Pawan K.
<x xml:space="preserve">Abstract</x> [1] We describe a new algorithm to retrieve SO2 from satellite‐measured hyperspectral radiances. We employ the principal component analysis technique in regions with no significant SO2 to capture radiance variability caused by both physical processes (e.g., Rayleigh and Raman scattering and ozone absorption) and measurement artifacts. We use the resulting principal components and SO2 Jacobians calculated with a radiative transfer model to directly estimate SO2 vertical column density in one step. Application to the Ozone Monitoring Instrument (OMI) radiance spectra in 310.5–340 nm demonstrates that this approach can greatly reduce biases in the operational OMI product and decrease the noise by a factor of 2, providing greater sensitivity to anthropogenic emissions. The new algorithm is fast, eliminates the need for instrument‐specific radiance correction schemes, and can be easily adapted to other sensors. These attributes make it a promising technique for producing long‐term, consistent SO2 records for air quality and climate research.